2010
DOI: 10.1037/a0018344
|View full text |Cite
|
Sign up to set email alerts
|

Are you happy for me? How sharing positive events with others provides personal and interpersonal benefits.

Abstract: Sharing good news with others is one way that people can savor those experiences while building personal and interpersonal resources. Although prior research has established the benefits of this process, called capitalization, there has been little research and no experiments to examine the underlying mechanisms. In this article, we report results from 4 experiments and 1 daily diary study conducted to examine 2 mechanisms relevant to capitalization: that sharing good news with others increases the perceived v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
330
2
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(357 citation statements)
references
References 109 publications
(133 reference statements)
13
330
2
4
Order By: Relevance
“…Indeed, past research maintains that individuals expect more social and psychological benefits by re-telling their positive experiences to relative strangers than close others (Reis et al, 2010;Tice et al, 1995). Furthermore, we can draw a parallel with other research asserting that males are more self-focused and females are more other focused, which influences their likelihood to give N-WOM to either strong ties or weak ties (Zhang, Feick & Mittal, 2014).…”
Section: Effect Of Wom On Self-enhancementsupporting
confidence: 58%
See 1 more Smart Citation
“…Indeed, past research maintains that individuals expect more social and psychological benefits by re-telling their positive experiences to relative strangers than close others (Reis et al, 2010;Tice et al, 1995). Furthermore, we can draw a parallel with other research asserting that males are more self-focused and females are more other focused, which influences their likelihood to give N-WOM to either strong ties or weak ties (Zhang, Feick & Mittal, 2014).…”
Section: Effect Of Wom On Self-enhancementsupporting
confidence: 58%
“…We posit that the effect of P-WOM on the sender's self-enhancement will be stronger for weak ties than strong ties. This is because past research has found that individuals expect to reap more social and psychological benefits such as establishing positive impression of themselves by retelling their positive experiences to relative strangers than to close others (Reis et al, 2010;Tice et al, 1995).…”
Section: Role Of Tie Strength As a Moderatormentioning
confidence: 99%
“…The strong role of trait influences in capitalization support is noteworthy because capitalization support is construed as a social process (Gable & Reis, 2010;Reis et al, 2010). Like perceived support, active-constructive support had stronger social than trait influences.…”
Section: Discussionmentioning
confidence: 98%
“…To determine if perceived and capitalization support have similar links to other constructs, we examined constructs that have been linked to either perceived or capitalization support in previous research: positive affect (Gable et al, 2004;Lakey & Scoboria, 2005;Reis et al, 2010), low negative affect (Gable & Reis, 2010;Lakey & Scoboria, 2005), and low interpersonal conflict (Gable et al, 2004;Lakey & Scoboria, 2005). Although all of these constructs have been linked to perceived or capitalization support previously, they have not been studied in the same samples, making it difficult to examine the extent to which perceived and capitalization support overlap.…”
mentioning
confidence: 99%
“…The social sharing of positive events has several implications: It not only increases disclosers' personal well-being, but also enhances relational well-being between disclosers and listeners (Gable, Reis, Impett, & Asher, 2004;Langston, 1994;Reis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%